Cyber Resilience and Strategic Stability: Securing Nuclear Facilities in the Digital Age - Zaidi, Syed Muhammad Saad; Ehsan, Muhammad; Ghalib, Sardar Jehanzaib (Risk analysis, 2025)
In an era of increasing digitization, nuclear command systems and power plants are becoming vulnerable to cyberattacks that can disrupt operations and undermine deterrence. This article examines the evolving threat landscape, drawing on literature and documented incidents of cyber intrusions into nuclear systems to identify critical technical and policy vulnerabilities. It argues that such intrusions risk eroding second‐strike credibility and may create incentives for preemptive action, thereby destabilizing strategic balances. Although regulatory bodies and international organizations have issued cybersecurity guidelines for nuclear facilities, implementation remains inconsistent. To address these challenges, the study proposes a set of resilience measures encompassing advanced technical safeguards, specialized workforce training, the establishment of international norms, and enhanced crisis communication protocols. Strengthening the cyber resilience of both civilian and military nuclear assets is presented as an urgent imperative for maintaining global security and strategic stability in the digital age.